(untitled) (Medical Forum Monthly, 2023)
Objective: To screen male school children to determine the prevalence of various urological abnormalities and offer appropriate advice to the parents of children in whom abnormalities would be detected. Study Design: Descriptive / observational study. Place and Duration of Study: This study was conducted at the Departments of Urology, Multan Institute of Kidney Diseases, Multan and NMCH, Multan from January 2014 to December 2017. Materials and Methods: We studied 129 boys, aged 6 to 17 years, in four public sector elementary and secondary schools of the city. In addition to physical examination, all boys had ultrasonography of abdomen and pelvis done for detection of urological abnormalities. Results: The mean age of boys was 13.12±2.017 years. Urological abnormalities were identified in 84 (68.9%) boys. The most common abnormalities included varicoceles in 26%, inguinal hernia 7.75%, undescended testis 6.97%, hydrocele 3.87%, epididymal cysts 3.87% and urolithiasis 3.87%. Other abnormalities identified included: unilateral renal agenesis, ectopic kidney, ureteropelvic junction obstruction, unilateral small sized kidneys, micropenis and hypospadiasis. None of the parents of these children were aware of identified abnormalities. Conclusion: The present study has identified that a significant number of school boys have urological abnormalities. Three most common abnormalities were varicoceles, inguinal hernias and undescended testes. The renal abnormalities were identified in 9.3% boys. Careful screening of school children is necessary to avoid later complications.